2016
DOI: 10.3325/cmj.2016.57.51
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen preconditioning ameliorates blood-brain barrier damage induced by hypoxia through modulation of tight junction proteins in an in vitro model

Abstract: AimTo explore the effects of hyperbaric oxygen preconditioning (HBOP) on the permeability of blood-brain barrier (BBB) and expression of tight junction proteins under hypoxic conditions in vitro.MethodsA BBB in vitro model was constructed using the hCMEC/D3 cell line and used when its trans-endothelial electrical resistance (TEER) reached 80-120 Ω · cm2 (tested by Millicell-Electrical Resistance System). The cells were randomly divided into the control group cultured under normal conditions, the group cultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…In the in vitro model of blood-brain barrier, brain microvascular endothelial cells can be cultured and trans-endothelial electric potential, as a measure of barrier function, can be evaluated in different oxygen circumstances [34]. Mainly cell interactions, tight junctions and endothelial-pericyte interactions are damaged in blood-brain barrier dysfunction.…”
Section: Endothelial Cells Barrier and Inflammationmentioning
confidence: 99%
See 3 more Smart Citations
“…In the in vitro model of blood-brain barrier, brain microvascular endothelial cells can be cultured and trans-endothelial electric potential, as a measure of barrier function, can be evaluated in different oxygen circumstances [34]. Mainly cell interactions, tight junctions and endothelial-pericyte interactions are damaged in blood-brain barrier dysfunction.…”
Section: Endothelial Cells Barrier and Inflammationmentioning
confidence: 99%
“…Latest in vitro studies demonstrated that hypoxic damage of blood-brain barrier may be reversed via HBOT [34]. Hypoxia induced cellular endothelial fragmentation and impair of cell adhesion molecular.…”
Section: Endothelial Cells Barrier and Inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent laboratory research reported that in vitro hypo-oxygenation (hypoxia) can result in permeability changes of the blood brain barrier (BBB) ( 1 ). Such changes provide an opportunity for molecules (substances) normally excluded by the BBB to enter the brain and possibly be trapped, especially after the integrity of the BBB is restored.…”
mentioning
confidence: 99%